The Role of Celebrity Endorsers and Brand Awareness on Purchasing Decision through Trust in E-Commerce Consumers in Yogyakarta (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the effect of celebrity endorsers and brand awareness on purchasing decisions through trust in Tokopedia E-Commerce consumers in Yogyakarta. This research uses quantitative methods. The population is Tokopedia E-Commerec consumers in Yogyakarta. The sampling technique used is nonprobability sampling by distributing questionnaires to 100 respondents measured on a Likert scale. For data analysis techniques using multiple linear regression analysis methods. The results of this study indicate that celebrity endorsers (X1) have a positive and significant effect on purchasing decisions (Y) and trust (Z), brand awareness (X2) has a positive and significant effect on purchasing decisions (Y) and trust (Z), trust (Z) has a positive and significant effect on purchasing decisions (Y). And there is a positive and significant influence of celebrity endorsers and brand awareness on purchasing decisions through trust.